NAPLAN discourses: a systematic review after the first decade. - Rose, Judy; Low-Choy, Samantha; Singh, Parlo; Vasco, Daniela (Discourse: Studies in the Cultural Politics of Education, 2020)
In 2018 NAPLAN (National Assessment Program – Literacy and Numeracy) reached a 10-year milestone. Introduced in 2008 by the Australian Curriculum, Assessment and Reporting Authority (ACARA), NAPLAN assesses student literacy and numeracy in Years 3, 5, 7 and 9. As a key education reform in Australia, NAPLAN has provoked critical debate across public, political and academic fora. This study synthesises themes emerging from a quantitative systematic review of NAPLAN-related literature to identify the main discourses that have emerged in response to this large-scale standardised assessment programme. The dominant discourses coalesce around 'datafication', 'social justice', 'affect and emotion', and 'accountability and performativity'. The stakes are high in these discursive struggles around NAPLAN as large-scale standardised testing is reconstituting the purposes of education, the professionalism and professional identities of educators, and affecting parents and students' engagement in schooling.